Proton conduction at BaO-terminated (001) BaZrO3 surface using density functional theory - Kim, Ji-Su; Yang, Jin-Hoon; Kim, Byung-Kook; Kim, Yeong-Cheol (ELSEVIER SCIENCE BV, 2015)
We studied proton conduction at a BaO-terminated (001) BaZrO3 surface by using density functional theory. In order to evaluate the proton conductivity at the surface, the space charge layer and structural disorder models were introduced. In the BaO-terminated (001) BaZrO3 surface, a positively-charged proton and an oxygen vacancy were segregated at the surface layer with segregation energies of -0.96 and -0.42 eV, respectively; this results in the generation of the Schottky barrier height. The migration energy barrier of the proton at the surface was 1.03 eV, and was converted to the proton mobility at the surface. Based on the concentration and mobility of the proton, its conductivity at the surface was evaluated. We find that the surface impedes the proton conduction by six orders of magnitude more than bulk at 900 K. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: GRAIN-BOUNDARY CONDUCTIVITY; TOTAL-ENERGY CALCULATIONS; AUGMENTED-WAVE METHOD; BARIUM ZIRCONATE; SPACE-CHARGE; BASIS-SET; OXIDES; METALS